Tuning the optical bandgap of multi-walled carbon nanotube-modified zinc silicate glass-ceramic composites - Chan, Kar Fei; Mohd Zaid, Mohd Hafiz; Liza, Shahira; Mamat, Md Shuhazlly; Matori, Khamirul Amin; Endot, Nor Azam; Tanemura, Masaki; Yaakob, Yazid (Elsevier, 2021)
Novel glass-ceramic composites with optical bandgap tunability were synthesised. Zinc silicate powder (ZS) was mixed with multi-walled carbon nanotubes (MWCNTs) at various mass fractions (0, 1, 2, and 3 wt %), followed by argon sintering. X-ray diffraction (XRD) analysis revealed the structural change from an amorphous ZS phase to a crystalline willemite phase (Zn2SiO4) by adding MWCNTs, and the largest crystallite size was obtained for ZS with 2.0 wt% MWCNTs. Although the agglomeration of ZS and MWCNTs was observed by field emission scanning electron microscopy (FESEM), there was no chemical interaction between ZS and MWCNTs as confirmed by Fourier transform infrared spectroscopy (FTIR). MWCNTs enhanced the crystallisation, which led to the green emission of Zn2SiO4 blue-shifting from 572 nm to 557 nm. The narrowed optical bandgap of Zn2SiO4 was attributed to the MWCNT-induced exciton localised between the valence band and conduction band of Zn2SiO4. The bandgap tuning effect of MWCNTs potentially paved new ways to mass fabricate zinc silicate-based semiconductors with desirable optical bandgap energy Eg, which significantly benefits the sensor and laser-related industry.